A practical method for calculating thermally-induced stresses in pile foundations used as heat exchangers. (October 2020) - Liu, Ryan Yin Wai; Sailer, Eleonora; Taborda, David M.G.; Potts, David M.; Zdravković, Lidija
Abstract: Thermo-active piles are capable of providing both structural stability as foundations and low carbon heating and cooling as ground source heat exchangers. When subjected to heating or cooling, the soil surrounding the pile restricts its expansion or contraction, giving rise to thermally-induced axial stresses, which need to be considered during design. Previous numerical studies often assume axisymmetry of the problem and/or a simplification of the heating or cooling mechanism of the pile. To simulate accurately the development of thermally-induced axial stresses, this paper presents a computational study comprising three-dimensional fully coupled thermo-hydro-mechanical finite element analyses conducted using the Imperial College Finite Element Program (ICFEP), where the heating of a thermo-active pile is simulated by prescribing a flow of hot water through the heat exchanger pipes within the pile. The effects of pipe arrangement on thermally-induced axial stresses are investigated by considering three different cases – single U-loop, double U-loop and triple U-loop. Since three-dimensional analyses are computationally expensive, a simplified method using a combination of two-dimensional analyses is proposed to estimate the thermally-induced axial stresses, which is subsequently validated and shown to yield accurate results.